Answer:
(
35
12
,
13
6
)
Step-by-step explanation:
−
2
x
+
8
=
2
x
5
+
1
y
=
x
(
2
5
)
+
1
Move all terms containing
x
to the left side of the equation.
Tap for more steps...
−
12
x
5
+
8
=
1
y
=
x
(
2
5
)
+
1
Move all terms not containing
x
to the right side of the equation.
Tap for more steps...
−
12
x
5
=
−
7
y
=
x
(
2
5
)
+
1
Multiply both sides of the equation by
−
5
12
.
−
5
12
⋅
(
−
12
x
5
)
=
−
5
12
⋅
−
7
y
=
x
(
2
5
)
+
1
Simplify both sides of the equation.
Tap for more steps...
x
=
35
12
y
=
x
(
2
5
)
+
1
Simplify each term.
Tap for more steps...
x
=
35
12
y
=
2
x
5
+
1
Replace all occurrences of
x
in
y
=
2
x
5
+
1
with
35
12
.
x
=
35
12
y
=
2
(
35
12
)
5
+
1
Simplify
2
(
35
12
)
5
+
1
.
Tap for more steps...
x
=
35
12
y
=
13
6
The solution to the system of equations can be represented as a point.
(
35
12
,
13
6
)